Extraction and Characterization of Agricultural Discarded Sesbania Aculeata Stem Waste as Potential Alternate for Synthetic Fibers in Polymer Composites. Issue 15 (23rd November 2022) - Venkatesan, G.; Vignesh, V.; Nagarajan, K.J.; Krishnaraj, R.; Nagaprasad, N.; Vinayagar, K.
ABSTRACT: Natural fibers have a wide range of potential applications in green composite manufacturing industrial sectors due to their renewable eco-friendly nature and remarkable properties. In the present work, the physico-chemical, thermal, tensile and morphological properties of Sesbania Aculeata Fibers (SAFs) are presented in first time. Chemical analysis results show that SAFs have relatively higher α-cellulose (70.1 wt.%) with lower hemicelluloses (10.2 wt.%), lignin (12.1 wt.%) and wax (0.6 wt.%) content. Structural analysis of SAFs was performed through fourier transform infrared (FTIR), energy dispersive X-ray microanalyzer (EDX) and NMR spectroscopy. X-ray diffraction (XRD) analysis evidenced that SAFs have a crystallinity index (CrI) of 65.5% with a crystalline size of 4.6 nm. The mechanical properties of the SAFs were investigated through a single fiber tensile test and fiber pull out test. The thermal stability of the SAFs was examined by thermogravimetric analysis (TGA). Based on the results, it is predicted that the SAFs can be used as a potential reinforcement in the polymer matrix composite structure.